207k views
18 votes
PLEASE HELP MEE RN! DUE IN 5 MINS SHOW YOUR WORK PLEASE

directions: solve the solution using substitution.

PLEASE HELP MEE RN! DUE IN 5 MINS SHOW YOUR WORK PLEASE directions: solve the solution-example-1
User Kcwu
by
4.9k points

1 Answer

5 votes

Answer:

x = 0

y = -12

Explanation:

Plug in what y is equal to into the second equation

-3(x - 12) = 2x + 36

Distribute the -3

-3x + 36 = 2x + 36

-36 -36

-3x = 2x

They cannot be equal so x = 0

Plug in 0 into the y equation

y = 0 - 12

y = -12

User Kavita Patil
by
4.7k points